Emerging roles of cancer-associated histone mutations in genomic instabilities - Yadav, Priyanka; Jain, Ronit; Yadav, Rajesh Kumar (Frontiers in Cell and Developmental Biology, 2024)
Epigenetic mechanisms fuel the quick evolution of cancer cells from normal cells. Mutations or aberrant expressions in the enzymes of DNA methylation, histone posttranslational modifications and chromatin remodelers are well investigated in cancer pathogenesis, however, cancerassociated histone mutants have gained momentum in the recent decade. Next-generation sequencing of cancer cells has identified somatic recurrent mutations in all the histones (H3, H4, H2A, H2B and H1) with various frequencies in various tumour types. Importantly, wellcharacterized H3K27M, H3G34R/V, and H3K36M mutations are termed as onco-histone mutants because of their wide role from the defect in cellular differentiation, transcriptional dysregulation, perturbed epigenomic profiles to genomic instability. Mechanistically, these histone mutants impart their effect on histone modifications and/or on irregular distribution of chromatin complexes. Recent studies identify the crucial role of H3K27M and H3G34R/V mutants in the DNA Damage Response (DDR) pathway but their impact on chemotherapy and tumour progression remains elusive. In this review, we have summarized the new developments in their function toward genomic instability and tumour progression. Finally, how this mechanistic understanding can be harnessed toward the potential treatment for tumours harbouring H3K27M, H3G34R/V, and H3K36M mutation.